Experiências docentes em tempos de pandemia de COVID-19: o papel das tecnologias digitais e o ensino de estudos amazônicos no município de Marituba-PA - SILVA FILHO, Lélio Barbosa da (2023)
In March 2020, a state of public calamity was declared in Brazil due to the increase in Covid-19 infections. As a result, there was a need to limit the circulation and gathering of people. Amidst this restrictive change, school activities were directly affected. The aim of this thesis was to analyze the performance of teachers in the discipline of Amazonian Studies in the face of the suspension of in-person teaching activities caused by the pandemic in the municipality of Marituba, PA. This reality demanded the search for new pedagogical practices, leading those involved to adapt to new teaching models that addressed the social and structural demands of individuals within the school community. For this study, we intend to understand the various issues that emerged for the teachers, discuss the incorporation of technological resources in the design and implementation of pedagogical proposals and educational actions, and explore approaches that encompass local content, aiming to value regional characteristics and foster the construction of socio-cultural identity.